Determination Of Total Flavonoid Content Of Young Suji Leaf Extract (Dracaena angustifolia) Using Thin Layer Chromatography And Uv-Vis Spectrophotometry Methods - Salniati; Evi Mustiqawati; Muhammad Tasjiddin Teheni (International Journal of Multidisciplinary Learners, 2024)
Dracaena angustifolia Roxb or better known as the suji plant has long been known in Indonesia, in its use as medicine, generally the part that is used is the leaves. Suji is said to have several compounds such as saponins, flavonoids, steroids and phenolic compounds. The most abundant polyphenol compound in suji leaf plants is flavonoids. Even so, the levels of flavonoids in a plant have different levels, both in tissue, plant age and environmental factors, and such as temperature, ultraviolet light, nutrition, water availability, and C02 levels in the atmosphere. Suji leaves can also be used for anti-inflammatory drugs, anti-dysentery, beriberi, gonorrhea and menstrual pain medication. The purpose of the study was to determine the presence of flavonoid compounds and the total flavonoid content of young suji leaf extract. The research sample was taken from Lahumoko Village, Kambowa District. This type of research is qualitative and quantitative using thin layer chromatography and uv-vis spectrophotometry methods. In the Thin Layer Chromatography (TLC) method, the mobile phase used is n-hexane: ethyl acetate (3:7), the visibility of spots on the TLC plate is assisted by UV light 366 nm. Determination of the flavonoid content of young suji leaves using UV-Vis spectrophotometry 366 nm. The results of the study contained flavonoid compounds as seen from the change in greenish yellow color and the total flavonoid compound content of young suji leaves was 291,731 mgRE/g. by 366 nm UV light. The determination of flavonoid content of young suji leaves was determined using UV-Vis 366 nm spectrophotometry. The results of the study showed a variety of flavonoids with a greenish-yellow color change and the level of flavonoid compounds in the total extract of young suji leaves was 291,731 mgRE/g